2019
DOI: 10.3390/ani9121126
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds in Pig Nutrition

Abstract: Simple Summary: In pig nutrition, alternative and safe supplements are needed to enhance the pigs' health and welfare. Natural feed components, such as herbs and plant extracts, are of great importance in animal nutrition, and marine macroalgae can be considered as supplements positively influence animal health parameters. Seaweeds possess several bioactive molecules that are studied for their prebiotic, anti-microbial, antioxidant, anti-inflammatory and immunomodulatory effects. Seaweed benefits are related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 120 publications
1
80
0
Order By: Relevance
“…In the present study, some numerical improvement (statistically non‐significant) in DM or CP digestibility was observed in the group fed with 1 g kg −1 aqueous extract of the red sea weed as compared to the control. In case of pigs, some of the seaweed species were shown to have no effect on digestibility, but some other species showed positive effect on N and gross energy digestibility 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, some numerical improvement (statistically non‐significant) in DM or CP digestibility was observed in the group fed with 1 g kg −1 aqueous extract of the red sea weed as compared to the control. In case of pigs, some of the seaweed species were shown to have no effect on digestibility, but some other species showed positive effect on N and gross energy digestibility 41 …”
Section: Discussionmentioning
confidence: 99%
“…also reported that incorporation of dried intact red sea weed K. alvarezii in broiler chicken diet @12.5 g kg −1 resulted in improved BW gain. In a review on effect of sea weeds on growth of piglets, it was noted that the average daily gain in BW of piglets fed brown seaweeds was higher than that of piglets fed a control diet with an increment of between +4.6 and + 40.8% 41 . It was suggested that positive effects of sea weeds on growth are related to the improvement in digestibility and overall health conditions of animals due to the prebiotic effects of seaweed polysaccharides, improvement in antioxidant status and the decrease in inflammatory condition, which may contribute to reduced energy and amino acidic expenditure 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that dietary brown seaweeds in livestock had a positive effect on health, growth performance, and meat quality due to their nutraceuticals properties and content of sulfated polysaccharides, phlorotannins, diterpenes, omega-3 polyunsaturated fatty acids, minerals and vitamins [ 11 , 12 ]. Moreover, brown seaweeds represent a renewable and sustainable feed ingredient for their high productivity if compared to other conventional ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, VFAs produced in the large intestine contribute up to 11% of the total energy requirements in pigs, while the VFAs produced in the total hindgut contribute up to 25% of the energy requirements [ 9 ]. In particular, some VFAs like butyrate, are involved in the development of colonocytes, which leads to proper gut maturation [ 10 , 11 ]. They have also been shown to reduce the growth of potential pathogens (e.g., Clostridium and Salmonella ) and to promote the growth of beneficial bacteria (e.g., Lactobacilli spp.)…”
Section: Introductionmentioning
confidence: 99%